PENGARUH KULIAH ONLINE TERHADAP MOTIVASI BELAJAR MAHASISWA DI DAERAH JABODETABEK SELAMA MASA PANDEMIK COVID-19 - Melkianus Albin Tabun (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2021)
This study aims to determine whether online lectures have a positive and significant effect on student learning motivation at tertiary institutions in the Greater Jakarta area (Jakarta-Bogor-Depok-Tangerang-Bekasi) during the covid-19 pandemic. Data collection used a questionnaire in the form of google form which was distributed to 200 respondents. The data analysis method used is descriptive analysis and simple linear regression analysis. Based on the results of the descriptive analysis of the research variables, it was found that basically online lectures were not as effective and efficient as face-to-face lectures, online lectures during the Covid-19 pandemic did not run as optimally and as optimally as face-to-face lectures. Meanwhile, based on the results of simple linear regression analysis, online lectures have a positive effect on student learning motivation at tertiary institutions in the Jabodetabek area.